Augmented and virtual reality effects on social responsibility in retail. (30th August 2022) - Wenzel, Kaylyn; Copeland, Lauren
The purpose of this research is to understand how knowledge of social responsibility within the apparel industry creates a sense of social responsibility concern, which would lead to purchase intention, while being moderated with the use and perception of virtual reality (VR) and/or augmented reality (AR). An online survey of 214 Gen Z respondents was conducted to understand participants' thoughts and familiarity with AR/VR. Overall, it was found that AR and VR are tools Gen Z is willing to use within their shopping experience, if given more experience with it.